2019
DOI: 10.1038/s41598-019-39451-4
|View full text |Cite
|
Sign up to set email alerts
|

Improved hole injection for blue phosphorescent organic light-emitting diodes using solution deposited tin oxide nano-particles decorated ITO anodes

Abstract: Blue phosphorescent organic light-emitting diodes (PHOLEDs) were fabricated with tin oxide (SnOx) nano-particles (NPs) deposited at the ITO anode to improve their electrical and optical performances. SnOx NPs helped ITO to increase the work function enhancing hole injection capability. Charge balance of the device was achieved using p- and n-type mixed host materials in emissive layer and the devices’ luminance and maximum external quantum efficiency (EQE) increased about nearly 30%. Tuning the work function u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…The improved performance may be attributed to higher hole-mobilities and reduced hole-injection barriers between the HIL and HTL as well as between the HTL and EML. 54–56 The phenothiazine substituted fluorene cored materials displayed a higher performance as compared to phenoxazine substituted fluorene cored materials. The reason why the devices show performance enhancement is due to their higher triplet energy ( E T ) values, having deep HOMO levels and high hole-mobilities, as shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The improved performance may be attributed to higher hole-mobilities and reduced hole-injection barriers between the HIL and HTL as well as between the HTL and EML. 54–56 The phenothiazine substituted fluorene cored materials displayed a higher performance as compared to phenoxazine substituted fluorene cored materials. The reason why the devices show performance enhancement is due to their higher triplet energy ( E T ) values, having deep HOMO levels and high hole-mobilities, as shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…3, the J – V curve of the Au,Li:VO x HOD almost overlaps with that of the EOD, which suggests that the value of γ is close to 1 and the number of holes and electrons in the device tends to be balanced. 48 To summarize, the increase of the electrical conductivity of the Au,Li:VO x film can promote the hole-injection, in turn, resulting in an improved carrier balance in the device. In contrast to the VO x HIL-based device, improved carrier balance is expected to improve device efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…Modifications have been applied to both anode/organic and cathode/organic interfaces, which intends to 1) reduce the injection barrier through modification of electrode work function or introduction of an interfacial charge separation layer/dipole layer, 2) narrow the injection barrier through the interfacial doping to enable tunneling, and 3) reinforce the interfacial electric fields for carrier injection by modification of the electrode surface. Utilization of NPs has been demonstrated as an effective and versatile strategy for carrier injection enhancements at electrode/organic interfaces due to the variable and unique electronic properties of NPs, and a variety of NPs [ 41–56 ] have been incorporated into various layers of OLEDs for carrier injection abilities improvement.…”
Section: Various Roles Of Nps In Oledsmentioning
confidence: 99%
“…In addition, metal oxide NPs such as Fe 3 O 4 , [ 45,46 ] NiO x , [ 47 ] SnO 2 , [ 48,49 ] MoO 3 , [ 54 ] ZnO, [ 55 ] TiO 2 , [ 56 ] etc., have also been introduced as efficient buffer layer or carrier injection layer in OLEDs, which also resulted in improved carrier injection abilities and thus device efficiencies. Sun's group demonstrated that Fe 3 O 4 modified anode in both bottom and top emitting OLEDs enables improved hole injection from anode and thus enhanced device efficiency, which stemmed from the formation of dipole layer and thus reduced hole injection barrier at the anode/organic interfaces (Figure 2f).…”
Section: Various Roles Of Nps In Oledsmentioning
confidence: 99%